The Birth of Sports Sociology and the Leicester Historical-Sociological School - A. S. Adelfinsky (Социология власти)
The review describes the origins of sports sociology in Great Britain within the "Leicester School" of Historical Sociology of Norbert Elias, explaining the causes for the strong influence of the ideas of Elysianism on the present-day international sociology of sports. The paper is based on an informal interview in 2010 with Eric Dunning, the founding father of the British Sociology of Sport, co-author and student of Norbert Elias. The overall development of the historical and sociological "Leicester School" of the 1960s and 1970s, its influence on the sociology of Great Britain, as well as the role of Elias and Ilya Neustadt in its formation are shown. The contemporary historical and sociological tradition of social analysis, inspired by the ideas of Elias and called the 'sociology of process' or 'figurative research', is described. Its key features are indicated: focus on relations-in-progress, relativism, studies of phenomena in their dynamics, the collection of historical materials, comparative analysis, and interdisciplinarity. The seminal works of Dunning and Elias on sports sociology are considered, in addition to the early development of this field of studies. It is noted that both authors viewed sport and leisure activities as a means to understand society and proposed a sociological interpretation of sport as a tool for the civilizational process. Their work was based not only on a theoretical framework, but also on extensive historical research. This contributed to the early acceptance of the ideas of Leicester School during the establishment of international sports sociology in the 1960s.